“Wise priest”: dominant agent in the religious field - Panteleeva, Anna (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2023)
The article presents the results of a study conducted in one of the parishes of the Lipetsk region from 2019 to 2022. The study took place in two stages: the first stage took place in July-August 2019, the second - in July-August 2022. The study used predominantly non-included observation. During the study, the author kept observation diaries. On the example of the parish of D., the author of the article studied, described and analyzed the practices of interaction between the priest and parishioners.The theoretical sources of the study were the works of P. Bourdieu. In the article we pay special attention to the possibilities of applying the theoretical model of P. Bourdieu in the study of religious tradition. Our results show that, despite not certain limitations, the theoretical framework we have chosen allows us to see and describe the unmanifested mechanisms that affect the interaction between the priest and parishioners.One of the features of the arrival of D., which aroused research interest, was its rather high degree of conflict. For a long period, the parishioners quite actively and uncompromisingly clashed with all the priests who were appointed to this parish. The situation changed not so long ago, after the appointment of Fr. A. The new priest managed to build a more balanced relationship with the arrival and stop the demonstratively defiant behavior of the parishioners.The conflict between priest and parishioner can be described in terms of habitus, fields, capital, and the hierarchy of the dominant positions of the field. These observations allow us to state that in the conflict between the priest and the parish, the conflict of two habituses is manifested, the carriers of which are, on the one hand, the priest, and on the other, the parishioners. The basis for updating the contradictions is the reduction of the distance, both physical and social, between the priest and the parish, as well as the fundamental impossibility of an effective transfer of capital between fields.Overcoming conflicts, we assume, may be associated with the restoration of social distance and the efforts of the priest to change mental structures, which should subsequently lead to a change in the habitus of parishioners.